SAT1000 - P759

Geometry Level 2

As shown above, the line: x 3 y + m = 0 ( m 0 ) x-3y+m=0\ (m \neq 0) intersects with the two asymptotes of the hyperbola:

x 2 a 2 y 2 b 2 = 1 ( a > 0 , b > 0 ) \dfrac{x^2}{a^2}-\dfrac{y^2}{b^2}=1\ (a>0,b>0) at point A , B A,B .

If point P P is at ( m , 0 ) (m,0) and P A = P B |PA|=|PB| , find the eccentricity of the hyperbola.

Let E E denote the eccentricity, submit 1000 E \lfloor 1000E \rfloor .


Have a look at my problem set: SAT 1000 problems


The answer is 1118.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Equations of asymptotes of given hyperbola is y = b a x \displaystyle y = \frac{b}{a}x and y = b a x \displaystyle y = -\frac{b}{a}x .

Points A A and B B can be determined by the intersection of each asymptote with the line: x 3 y + m = 0 \displaystyle x - 3y + m = 0 . We get

A = ( m a 3 b + a , m b 3 b + a ) B = ( m a 3 b a , m b 3 b + a ) \displaystyle A = \bigg(\frac{-ma}{3b + a},\frac{mb}{3b + a}\bigg)\hspace{50pt} B = \bigg(\frac{ma}{3b - a},\frac{mb}{3b + a}\bigg)

Point P P is at ( m , 0 ) \displaystyle (m,0) .

P A 2 = ( m m a 3 b + a ) 2 + ( 0 m b 3 b + a ) 2 \displaystyle PA^2 = \bigg(m - \frac{-ma}{3b + a}\bigg)^2 + \bigg(0 - \frac{mb}{3b + a}\bigg)^2

P A 2 = m 2 + m 2 a 2 ( 3 b + a ) 2 + 2 m 2 a 3 b + a + m 2 b 2 ( 3 b + a ) 2 \displaystyle \Rightarrow PA^2 = m^2 + \frac{m^2a^2}{(3b + a)^2} + \frac{2m^2a}{3b + a} + \frac{m^2b^2}{(3b + a)^2}

P A 2 = m 2 ( ( 3 b + a ) 2 + a 2 + 2 a ( 3 b + a ) + b 2 ( 3 b + a ) 2 ) \displaystyle \Rightarrow PA^2 = m^2\bigg(\frac{(3b + a)^2 + a^2 + 2a(3b + a) + b^2}{(3b + a)^2}\bigg)

P A 2 = m 2 ( 4 a 2 + 10 b 2 + 12 a b ) ( 3 b + a ) 2 Eq. 1 \displaystyle\Rightarrow PA^2 = \frac{m^2(4a^2 + 10b^2 + 12ab)}{(3b + a)^2}\hspace{35pt}\cdots\hspace{15pt}\text{Eq. 1}

Similarly, writing for P B 2 PB^2

P B 2 = ( m m a 3 b a ) 2 + ( 0 m b 3 b a ) 2 \displaystyle PB^2 = \bigg(m - \frac{ma}{3b - a}\bigg)^2 + \bigg(0 - \frac{mb}{3b - a}\bigg)^2

P B 2 = m 2 + m 2 a 2 ( 3 b a ) 2 2 m 2 a 3 b a + m 2 b 2 ( 3 b a ) 2 \displaystyle \Rightarrow PB^2 = m^2 + \frac{m^2a^2}{(3b - a)^2} - \frac{2m^2a}{3b - a} + \frac{m^2b^2}{(3b - a)^2}

P B 2 = m 2 ( ( 3 b a ) 2 + a 2 2 a ( 3 b a ) + b 2 ( 3 b a ) 2 ) \displaystyle \Rightarrow PB^2 = m^2\bigg(\frac{(3b - a)^2 + a^2 - 2a(3b - a) + b^2}{(3b - a)^2}\bigg)

P B 2 = m 2 ( 4 a 2 + 10 b 2 12 a b ) ( 3 b a ) 2 Eq. 2 \displaystyle\Rightarrow PB^2 = \frac{m^2(4a^2 + 10b^2 - 12ab)}{(3b - a)^2}\hspace{35pt}\cdots\hspace{15pt}\text{Eq. 2}

It is given that P A = P B |PA| = |PB|

P A 2 = P B 2 \displaystyle\Rightarrow PA^2 = PB^2

Putting the expressions of P A 2 PA^2 and P B 2 PB^2 from Eq. 1 and Eq. 2 in the above equation we get

m 2 ( 4 a 2 + 10 b 2 + 12 a b ) ( 3 b + a ) 2 = m 2 ( 4 a 2 + 10 b 2 12 a b ) ( 3 b a ) 2 \displaystyle \frac{m^2(4a^2 + 10b^2 + 12ab)}{(3b + a)^2} = \frac{m^2(4a^2 + 10b^2 - 12ab)}{(3b - a)^2}

2 a 2 + 5 b 2 + 6 a b ( 3 b + a ) 2 = 2 a 2 + 5 b 2 6 a b ( 3 b a ) 2 \displaystyle \Rightarrow \frac{2a^2 + 5b^2 + 6ab}{(3b + a)^2} = \frac{2a^2 + 5b^2 - 6ab}{(3b - a)^2}

( 3 b + a ) 2 2 a 2 + 5 b 2 + 6 a b = ( 3 b a ) 2 2 a 2 + 5 b 2 6 a b [ \displaystyle \Rightarrow \frac{(3b + a)^2}{2a^2 + 5b^2 + 6ab} = \frac{(3b - a)^2}{2a^2 + 5b^2 - 6ab}\hspace{25pt}[ Reciprocating both sides ] ]

a 2 + 9 b 2 + 6 a b 2 a 2 + 5 b 2 + 6 a b = a 2 + 9 b 2 6 a b 2 a 2 + 5 b 2 6 a b \displaystyle \Rightarrow \frac{a^2 + 9b^2 + 6ab}{2a^2 + 5b^2 + 6ab} = \frac{a^2 + 9b^2 - 6ab}{2a^2 + 5b^2 - 6ab}

1 + 4 b 2 a 2 2 a 2 + 5 b 2 + 6 a b = 1 + 4 b 2 a 2 2 a 2 + 5 b 2 6 a b \displaystyle \Rightarrow 1 + \frac{4b^2 - a^2}{2a^2 + 5b^2 + 6ab} = 1 + \frac{4b^2 - a^2}{2a^2 + 5b^2 - 6ab}

4 b 2 a 2 2 a 2 + 5 b 2 + 6 a b = 4 b 2 a 2 2 a 2 + 5 b 2 6 a b \displaystyle \Rightarrow \frac{4b^2 - a^2}{2a^2 + 5b^2 + 6ab} = \frac{4b^2 - a^2}{2a^2 + 5b^2 - 6ab}

Above equation is true only if numerator is 0 0 or denominators are equal. Denominator can be equal when any one of a a or b b is 0 0 which is not possible for existence of hyperbola. So numerator must be 0 0 .

4 b 2 a 2 = 0 \displaystyle \Rightarrow 4b^2 - a^2 = 0

a 2 b 2 = 4 b 2 a 2 = 1 4 \displaystyle \Rightarrow \frac{a^2}{b^2} = 4 \Rightarrow \frac{b^2}{a^2} = \frac{1}{4}

Eccentricity of hyperbola is given by E = 1 + b 2 a 2 \displaystyle E = \sqrt{1 + \frac{b^2}{a^2}}

So, E = 1 + 1 4 = 5 4 = 5 2 \displaystyle E = \sqrt{1 + \frac{1}{4}} = \sqrt{\frac{5}{4}} = \frac{\sqrt{5}}{2}

1000 E = 1000 5 2 = 500 5 1118.034 \displaystyle \Rightarrow 1000E = 1000\frac{\sqrt{5}}{2} = 500\sqrt{5} \approx 1118.034

1000 E = 1118 \displaystyle \Rightarrow \lfloor 1000E \rfloor = 1118

A more easier approach would be to draw a circle with P as centre and PA or PB as radius

TAPAS YOGI - 5 months, 2 weeks ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...